The intravenous route to blood glucose control. - Parker, R.S.
This article discusses closed-loop blood glucose regulation algorithms that use the intravenous route for insulin delivery to insulin-dependent diabetic patients. Classical control methods and advanced algorithms using implicit knowledge or explicit models (empirical, fundamental, or ?gray-box?) of the diabetic patient are examined. Current research on characterizing patient variability is presented, in the context of a model predictive controller able to adjust to changes in patient glucose and insulin sensitivity
Keywords: Advanced algorithms; Classical control methods; Control algorithms; Explicit models; Implicit knowledge; Insulin sensitivity; Intravenous route; Model predictive controller; Noninvasive monitoring; Patient glucose changes; Patient variability; Type I diabetic patients